2018
DOI: 10.3389/fvets.2018.00216
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids and Potential for Modifying the Avian Gastrointestinal Tract and Reducing Pathogens and Disease

Abstract: Recently, antibiotics have been withdrawn from some poultry diets; leaving the birds at risk for increased incidence of dysbacteriosis and disease. Furthermore, mortalities occurring from disease contribute between 10 to 20% of production cost in developed countries. Currently, numerous feed supplements are being proposed as effective antibiotic alternatives in poultry diets, such as prebiotics, probiotics, acidic compounds, competitive exclusion products, herbs, essential oils, and bacteriophages. However, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
167
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 129 publications
2
167
0
3
Order By: Relevance
“…In addition, Wang et al 37 showed that lactic acid could even completely inhibit growth of pathogens inclusive of E. coli, Salmonella and L. monocytogenes. The others include physical blocking of available bacterial receptor sites 32,38,39 ; compete with pathogenic bacteria for essential nutrients and energy source; secretion of antimicrobial substances and release of selective gut protective metabolites like arginine, glutamine, short-chain fatty acids and conjugated linoleic acids. 35,40…”
Section: Competitive Exclusion Of Pathogenic Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Wang et al 37 showed that lactic acid could even completely inhibit growth of pathogens inclusive of E. coli, Salmonella and L. monocytogenes. The others include physical blocking of available bacterial receptor sites 32,38,39 ; compete with pathogenic bacteria for essential nutrients and energy source; secretion of antimicrobial substances and release of selective gut protective metabolites like arginine, glutamine, short-chain fatty acids and conjugated linoleic acids. 35,40…”
Section: Competitive Exclusion Of Pathogenic Microorganismsmentioning
confidence: 99%
“…The common mechanisms of bacteriocin-mediated killing include the destruction of target cells by pore formation and/or inhibition of cell wall synthesis. 39,40…”
Section: Production Of Antimicrobial Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to SCFAs, organic acids also entail medium chain fatty acids (MCFAs) which are 6 to 12 carbons in length, and long chain fatty acids (LCFAs ≥ 13C) (Beermann et al, 2003). Short chain fatty acids are produced in the gastrointestinal tract (GIT) of chickens and humans and have been extensively studied as potential poultry GIT modifiers for pre-harvest intervention as animal feed additives (Cherrington et al, 1991;Ricke, 2003;Van Immerseel et al, 2006;Dittoe et al, 2018a). These fatty acids have also been utilized as sanitizers, although less information is available from the literature.…”
Section: Alternative Acidifiers Used In Poultry Productionmentioning
confidence: 99%
“…Lauric and myristic acids inhibit Clostridium perfringens at concentrations of 0.1 to 0.2 mg/ml (Skrivanová et al, 2006). However, the lipopolysaccharide layer of Gramnegative bacteria has been shown to elicit resistance against MCFAs and LCFAs by preventing the fatty acids from crossing the cell membrane (Sheu and Freese, 1973;Cherrington et al, 1991;Dittoe et al, 2018a). Citric acid, another organic acid, has been shown to inhibit C. perfringens at a concentration of 4 mg/ml and has antimicrobial properties against Gram-negative bacteria (Skrivanová et al, 2006;Over et al, 2009;DoleŽalová et al, 2010).…”
Section: Alternative Acidifiers Used In Poultry Productionmentioning
confidence: 99%